SOSIALISASI AGRESIVITAS VERBAL PADA REMAJA DI DESA SUKAMUKTI - Ciptaningtyas, Yulia; Paryati, Ninik; Supratno , Setyo (Universitas Islam 45 Bekasi, 2024)
A preliminary study in Sukamukti Village indicates that teenagers often use offensive language, mockery, insults, slander, derogatory remarks, and threats in their interactions, and they view this behavior as normal. To address this issue, a community-based empowerment program was designed targeting junior high school students in the village. This program includes a pre-test, psychoeducation, a post-test, and discussions to enhance understanding of verbal aggressive behavior. Implementation methods involve planning, obtaining permissions, conducting activities, and data collection to evaluate improvements in participants' knowledge and behavior. This initiative aims to increase teenagers' awareness of verbal aggression. The program showed an improvement in understanding among Madrasah Ibtidaiyah students in Sukamukti Village, with 5 students, or 15.2%, reaching a high level of understanding.